KEPEMIMPINAN PENDIDIKAN ISLAM PERSPEKTIF HUMANIS - Nur Alip; Fina Ayu Madaliah; Ansori Ansori; Iwan Aprianto (MANAJERIAL : Jurnal Inovasi Manajemen dan Supervisi Pendidikan, 2026)
ABSTRACT Islamic educational leadership plays a strategic role in directing and managing educational institutions to achieve educational goals while fostering students' character based on Islamic values. Amid globalization and increasingly complex social changes, educational leadership is expected to promote not only academic achievement but also humanistic values that support holistic human development. This study aims to analyze the concept of Islamic educational leadership from a humanistic perspective, identify the humanistic values relevant to Islamic educational leadership, and explain their implementation in educational management. This study employed a qualitative approach using a library research method. Data were collected from secondary sources and analyzed using content analysis. The findings reveal that Islamic educational leadership from a humanistic perspective integrates the values of amanah (trustworthiness), justice, exemplary conduct, consultation (shūrā), empathy, and respect for human dignity into a leadership model encompassing spiritual, moral, social, personal, and human resource development dimensions. The implementation of this model fosters an inclusive, participatory, and democratic educational environment while promoting character formation and the holistic development of students. The integration of Islamic and humanistic values provides a conceptual foundation for developing adaptive, equitable, and relevant educational leadership to address contemporary educational challenges. ABSTRAK Kepemimpinan pendidikan Islam memiliki peran strategis dalam mengarahkan dan mengelola lembaga pendidikan untuk mencapai tujuan pendidikan sekaligus membentuk karakter peserta didik berdasarkan nilai-nilai Islam. Di tengah perkembangan globalisasi dan perubahan sosial yang kompleks, kepemimpinan pendidikan dituntut tidak hanya berorientasi pada pencapaian akademik, tetapi juga pada pengembangan nilai-nilai kemanusiaan. Penelitian ini bertujuan menganalisis konsep kepemimpinan pendidikan Islam dalam perspektif humanis, mengidentifikasi nilai-nilai humanisme yang relevan, serta menjelaskan implementasinya dalam pengelolaan lembaga pendidikan. Penelitian menggunakan pendekatan kualitatif dengan metode studi kepustakaan (library research). Data diperoleh dari berbagai sumber sekunder dan dianalisis menggunakan teknik content analysis. Hasil penelitian menunjukkan bahwa kepemimpinan pendidikan Islam perspektif humanis mengintegrasikan nilai amanah, keadilan, keteladanan, musyawarah, empati, dan penghormatan terhadap martabat manusia dalam model kepemimpinan yang mencakup dimensi spiritual, moral, sosial, personal, dan pengembangan sumber daya manusia. Implementasi model tersebut menciptakan lingkungan pendidikan yang inklusif, partisipatif, demokratis, serta mendukung pembentukan karakter dan pengembangan potensi peserta didik secara holistik. Integrasi nilai-nilai keislaman dan humanisme menjadi landasan konseptual bagi pengembangan kepemimpinan pendidikan yang adaptif, berkeadilan, dan relevan menghadapi tantangan pendidikan modern.